중추성 성조숙증의 진단과 치료 (The Ewha Medical Journal)
A notable secular trend in early puberty onset has been described over the past few decades. Also, the prevalence and incidence of precocious puberty is increasing not only in Korea, but also around the world. The manifestation of secondary sex characteristics before 8 years in girls and 9 years in boys is defined as precious puberty. The causes of precocious puberty can be classified as gonadotropin releasing hormone (GnRH)-dependent, also known as central precocious puberty (CPP), or GnRH-independent. Evaluation of patient with precocity requires detailed examination of the clinical manifestation, GnRH stimulation test, and imaging of the central nervous system if indicated. The standard treatment for CPP is GnRH agonist, which is beneficial for adequate pubertal development and preservation of final adult height. In this paper, we investigate the diagnosis and adequate treatment of CPP.